Collaborative Governance of One Data Indonesia in East Nusa Tenggara Province - Emanuel Yosep Lamawato; Ajis S. Adang Djaha; Nursalam . (Universitas Muhammadiyah Gorontalo, 2026)
This study aims to analyze the collaborative governance of One Data Indonesia (SDI) in East Nusa Tenggara Province (NTT) and to identify the obstacles encountered in its implementation. The research is grounded in empirical conditions in which, despite the existence of a national regulatory framework through Presidential Regulation Number 39 of 2019 reinforced by Governor Regulation Number 64 of 2020, regional data management still suffers from sectoral fragmentation, inconsistent indicators across the Regional Apparatus (PD), and limited interoperability within the SASANDO NTT Portal. A qualitative case study approach was applied, with data collected through in-depth interviews with key informants from Bapperida, Walidata at the Communication and Information Service, the Central Bureau of Statistics, and selected PDs, supplemented by non-participant observation and documentary analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while the four dimensions of collaborative governance proposed by Ansell and Gash (starting conditions, institutional design, facilitative leadership, and collaborative process) served as the analytical framework. The findings reveal that the collaborative governance of SDI in NTT has been formally established but remains substantively limited. Uneven human resource capacity across PDs, a weak data-sharing culture, and unevenly distributed facilitative leadership constrain the collaboration. Strengthening the Walidata mandate, accelerating data standardization, and embedding a data-driven governance culture are required to shift the collaboration from formal toward substantive engagement.